Pelatihan Pemasaran Digital Dalam Upaya Meningkatkan Usaha UMKM Pada Makaroni Nampol By MTH Foods - Rina Fitriani; Widiyawati Widiyawati; Siti Chodijah; Satria Satria; HS. Sulistyowati; Aidah Hami (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
The era of Industrial Revolution 4.0 and Society 5.0 in various walks of life is also felt by MSMEs who are expected to be able to adopt digital in product marketing, both through social media and various marketplaces. It is also important for an entrepreneur to manage relationships with his customers, both loyal customers and acquiring new customers. Customer data generated from interactions on social media and marketplaces can be used for promotions and minimizing costs. There is a gap between technological developments and digital skills in society, especially Makaroni Nampol by MTH Foods as an MSME that has just started using technological devices, which is the background for service and supporting the Tri Dharma Lecturers. Service method with Training and Mentoring which aims to provide an entrepreneurial mindset, improve the skills of business actors more deeply, such as: online NIB (Business Permit Number) registration, Google My Business, creating accounts on social media, product photography techniques, copywriting and creating BMC ( Business Model Canvas). As a result of this activity, the owner of the Makaroni Nampol by MTH Foods business was very enthusiastic about participating in the training and mentoring, asked a lot of questions in an effort to improve digital marketing, and after attending the training he was able to create a business account on the social media WA, Instagram and TikTok.